Prevalence of Burnout syndrome in nursing professionals from Orinoquia, Colombia in 2016 - Gutiérrez-Lesmes, Oscar Alexander; Loboa-Rodríguez, Nelly Johana; Martínez-Torres, Javier (Universidad y Salud, 2018)
Introduction: Burnout syndrome is described as an inadequate way of coping with labor stress. The main traits are emotional exhaustion, depersonalization and decreased personal performance. Objective: To determine the prevalence of Burnout syndrome in nursing professionals working in the Colombian Orinoquia. Materials and methods: A transverse analytical study was carried out with sampling by intention. The study population was constituted by 100 nurses and the Maslach Burnout instrument was used. Summary, prevalence and prevalence ratio measurements were calculated with the SPSS program. Results: 90% of the sample studied were women, 53% single, 54% under 28 and 42% without children. The general prevalence of Burnout syndrome was 16%, in the area of hospital care was 25.5% and in areas other than this was 6.1%. In the hospital area, there were greater proportions in emotional fatigue with a 42%, emotional depersonalization with a 38% and lack of personal realization with a 30%. Statistically significant differences for the prevalence of Burnout syndrome in the area of hospital care were found (RP 4.2, IC95% 1,3-13.7, P 0.008) for professionals under 28 (RP 3.7 IC95% 1.1-12.1, p 0.017). Conclusions: The prevalence of Burnout syndrome is higher in nurses in the hospital area. Being under 28 years of age was associated with a higher prevalence. Nurses classified as sick with Burnout syndrome had to take care of a greater number of patients in their workday.